Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1039/d1ce00810b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structures, dielectric and magnetic properties of manganese sulfonyldibenzoates

Abstract: Six coordination polymers based on Mn(ii) and V-shaped ligand were successfully isolated and their dielectric as well as magnetic behaviours were investigated. The paper also discusses the growth of solids in terms of supramolecular aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…In MnCP2 , two carboxylate groups of 2,4′- bpdc are bound to four Mn centers in a monodentate fashion ( κ 1 -κ 1 ) - ( κ 1 -κ 1 ) -μ 4 (Scheme S2b). The bond lengths (Mn–O) and bond angles (O–Mn–O) are in the range reported for similar solids. , As shown in Figure b, two triangular prismatic polyhedrons {MnO 4 N 2 } are bridged by 2,4′- bpdc forming the metal-carboxylate dimer; the dimers are extended into a 1D chain through 2,4′- bpdc (Figure ). Additional H-bonding interactions (Figure ) further stabilize the crystal packing: C–H···O between the phenanthroline benzyl ring and the carbonyl oxygen of 2,4′- bpdc from adjacent chains (H phen ···O and C phen ···O C=O , 2.508(2) and 3.360(4) Å).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…In MnCP2 , two carboxylate groups of 2,4′- bpdc are bound to four Mn centers in a monodentate fashion ( κ 1 -κ 1 ) - ( κ 1 -κ 1 ) -μ 4 (Scheme S2b). The bond lengths (Mn–O) and bond angles (O–Mn–O) are in the range reported for similar solids. , As shown in Figure b, two triangular prismatic polyhedrons {MnO 4 N 2 } are bridged by 2,4′- bpdc forming the metal-carboxylate dimer; the dimers are extended into a 1D chain through 2,4′- bpdc (Figure ). Additional H-bonding interactions (Figure ) further stabilize the crystal packing: C–H···O between the phenanthroline benzyl ring and the carbonyl oxygen of 2,4′- bpdc from adjacent chains (H phen ···O and C phen ···O C=O , 2.508(2) and 3.360(4) Å).…”
Section: Resultsmentioning
confidence: 57%
“…In MnCP3 , 2,4′- bpdc adopts two types of coordination modes: in one, two carboxylate groups are bonded symmetrically to four Mn centers through the monodentate mode ( κ 1 -κ 1 ) - ( κ 1 -κ 1 ) -μ 4 (Scheme S2c), while in the other, two carboxylate groups are bound to four Mn centers via both monodentate and bidentate fashion ( κ 1 -κ 1 ) - ( κ 1 -κ 2 ) -μ 4 (Scheme S2d). The bond lengths (Mn–O) and bond angles (O–Mn–O) are in the range expected for similar solids. , Selected bond lengths and bond angles for all the solids are listed in Table S8. As shown in Figure c, three distorted octahedra are bridged by 2,4′- bpdc to form the corner shared metal-carboxylate trimer {Mn 3 O 14 N 2 }; the trimers are extended into 2D sheets through 2,4′- bpdc (Figure ).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…At supersaturation, a finite number of tectons assemble through noncovalent interactions and spontaneously condense through a first-order phase transition. , Retroanalysis is a reliable method to picturize the nucleation of a crystal from condensing molecular building blocks. We have demonstrated this approach successfully in several inorganic and metal–organic solids. , Crystal packing observed in all the three solids 1–3 could be readily conceived considering the 1:1 manganese dicarboxylate complex as a tecton as shown in Figures a, a, and a. The figures show how the assembly of the tectons facilitates extended manganese carboxylate coordination favoring the layers.…”
Section: Resultsmentioning
confidence: 92%
“…The results suggested that the semirigid polycarboxylate ligand combined with rigid and flexible molecular backbones appears to tune the spin-exchange interactions owing to their various coordination modes such as syn–syn , anti–anti , syn-anti , and so on. The approach would provide a platform to rationalize the design from choosing molecular building blocks and thereby control magnetic interactions between different magnetic centers . This study prompted us to examine another flexible ligand, namely, 4,4′-benzophenone dicarboxylic acid ( H 2 bpdc ) that was less explored.…”
Section: Introductionmentioning
confidence: 99%